Assessment of the Nutritional Status and Skeletal Muscle Condition in Patients With Resectable Gastric Cancer - I. B. Uvarov; O. M. Asipovich; S. N. Derbenev; A. V. Yashchenko; D. V. Andreev; V. A. Porhanov; A. M. Manuilov (Инновационная медицина Кубани)
Background: Patients with gastric cancer (GC) are at high risk of nutrient deficiencies (ND) that can negatively affect the postoperative period and long-term treatment outcomes.Objective: To assess the nutritional status (NS) and skeletal muscle condition in patients with resectable stage I-III GC.Materials and methods: Our study included 102 GC patients: 64 men (62.7%) and 38 women (37.3%) aged 31 to 77 years. During the assessment we used the NRS-2002 system, determined laboratory markers of the NS, calculated the Nutritional Risk Index (NRI), and evaluated the condition of adipose tissue and skeletal muscles using computed tomography.Results: We found that 70.6% of the patients had ND: NRS-2002 score < 3 points (52%) and NRS-2002 score ≥ 3 points (18.6%). Risk factors for ND were tumor localization in the cardia and stage III GC. Laboratory markers of ND were transferrin and NRI. Among the examined patients (n = 80) sarcopenia was detected in 10 (12.5%) patients: 1 patient (1/25; 4.0%) from the group without ND, 6 patients (6/42; 14.3%) from the group with NRS-2002 score < 3 points, and 3 patients (3/13; 23.1%) from the group with NRS2002 score ≥ 3 points, (P = .212). In multivariate logistic regression analysis, independent factors associated with sarcopenia were age, body mass index, and total protein.Conclusions: All GC patients selected for radical surgery should undergo nutritional assessment using special tools (NRS-2002, NRI) and evaluation of the skeletal muscle condition. Sarcopenia may occur in patients with no clinical or laboratory evidence of ND. In GC patients at nutritional risk, preand postoperative nutritional support should be considered to reduce the ND-related risks.